Predictors of letter knowledge in children growing in poverty - Diuk, Beatriz Graciela (2011)
This study examined the influence of phonological processing abilities on letter knowledge and letter learning in 1st grade children growing in poverty. At the beginning of the school year, 59 first graders were evaluated with tests measuring phonological awareness, phonological memory and rapid naming. Letter knowledge was assessed at the beginning and at the end of the year. All phonological processing abilities predicted letter knowledge at time 1, with phonological awareness producing the largest effect. However, only phonological memory predicted additional letter learning during the school year, once initial letter knowledge was taken into account.